Rebar corrosion in mortars containing calcareous filler - Batic, O. R. (2010)
Ordinary portland cement can be replaced, partially, by mineral admixtures which modify the properties of concrete and influence rebar corrosion. The most common mineral admixtures are puzzolans, granulated blast furnace slag, calcareous filler, fly ash with high and low lime content, condensed silica fumes, and rice hush ash. There is an increasing tendency to incorporate carbonate additions to mortars. The beneficial effect of calcareous filler addition has been long discussed although not many studies have been made on the effect of this addition on rebar corrosion. In this research, rebar corrosion in mortar containing calcareous filler was studied employing two water/cement (w/c) ratios: 0.50 and 0.65, respectively. It was found that rebar corrosion became important as the w/c increased. The presence of calcium carbonate altered the structure of the passive layer on rebars.